Impact Of The Flipped Learning Model On Developing First Year Algerian Efl Degree Students’ Reading Ability: A Blended Learning Approach - Loubna Sebbah (Al-Lisaniyyat, 2019)
Flipped learning has garnered much attention from researchers since it is considered as an innovative instructional method that meshes online learning with face-to-face learning. Within the framework of sociocultural theory, this research study focuses on the use of mediation and collaboration in the learning process and aims at investigating the impact of flipped learning on deve- loping Algerian first year EFL degree students' reading ability at the university of Algiers 2 as well as exploring their perceptions of using flipped learning To this end, this research study is qua- si-experimental and consisted of 100 participants divided into 50 experimental subjects and 50 control subjects. Data were collected through administering a reading test to both groups under study and a perceptual questionnaire to the experimental group only. The findings reveal that flipped learning has significantly a positive im- pact on developing experimental subjects' reading ability. Moreo- ver. the experimental subjects expressed positive perceptions of using flipped learning to develop their reading skill. This research article concludes with pointing out some implications for imple- menting flipped learning in EFL classrooms and casts new light on this model.